Long-term safety and efficacy of sarilumab over 5 years in patients with rheumatoid arthritis refractory to TNF inhibitors. (19th April 2021) - Fleischmann, Roy; Genovese, Mark C; Maslova, Karina; Leher, Henry; Praestgaard, Amy; Burmester, Gerd R
Abstract: Objective: The objective of this study was to evaluate the long-term safety and efficacy of sarilumab over 5 years in patients with RA refractory to TNF inhibitors (TNFis). Methods: Patients in the 24-week randomized controlled trial (RCT) TARGET (NCT01709578) who received double-blind placebo or sarilumab 150 or 200 mg every 2 weeks (q2w), plus conventional synthetic DMARDs (csDMARDs), were eligible to receive open-label sarilumab 200 mg q2w plus csDMARDs in the open-label extension (OLE), EXTEND (NCT01146652). OLE dose reduction to 150 mg q2w was permitted per investigators' judgement or protocol-mandated safety concerns. Safety and efficacy were assessed through treatment-emergent adverse events (AEs), laboratory abnormalities and clinical DASs. All statistics are descriptive. Results: Of 546 patients, 454 (83%) were treated with sarilumab in the OLE. The cumulative observation period was 1654.8 patient-years (PY; n  =   521); 268 patients (51%) had ≥4 years' exposure. Incidence rates per 100 PY of AEs, and AEs leading to discontinuation, infection and serious infection were 160.4, 8.1, 57.8 and 3.9, respectively. Neutropenia was the most common AE (15.3 per 100 PY). An absolute neutrophil count of <1000 cells/mm 3 (Grade 3/4 neutropenia) was observed in 74 patients (14.2%) and normalized on treatment in 48. Clinical efficacy was sustained through 5 years' follow-up. Efficacy was similar for patients with 1 and >1 TNFi failure, and similar for patients who either remained on 200 mg or reduced to 150 mg. Conclusion: In patients with RA refractory to TNFi, sarilumab's long-term term safety profile was consistent with previous clinical studies and post-marketing reports. Efficacy was sustained over 5 years. Trial registration: TARGET, ClinicalTrials.gov, https://clinicaltrials.gov/ct2/show/NCT01709578, NCT01709578; EXTEND, ClinicalTrials.gov, https://www.clinicaltrials.gov/ct2/show/NCT01146652, NCT01146652.